Characterization of Fluoroalcohols-Induced Intermediates of Mucor miehei Lipase at Low pH - Fatima, Sadaf; Mishra, Aseem; Sen, Priyankar; Khan, Rizwan H. (Protein and Peptide Letters, 2008)
We have previously characterized an acid-unfolded (UA) state of Mucor miehei lipase at pH 2. The effect of 2,2,2-trifluoroethanol (TFE) and 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) resulted in characterization of molten-globule (MG) like states with β-sheet secondary structure at 15% (v/v) TFE and 6% (v/v) HFIP. α-Helical states accumulate at 80% (v/v) TFE and 30% (v/v) HFIP.
Keywords: circular dichroism